2023
DOI: 10.1002/vms3.1225
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of avian schistosome Trichobilharzia regenti (Schistosomatidae, Digenea) from naturally infected hosts in northern Iran

Abstract: BackgroundTrichobilharzia regenti (T. regenti) is an avian schistosomatid fluke species that causes human cercarial dermatitis (HCD) in areas of aquaculture in northern Iran. Understanding the phylogenetic relationships and genetic diversity of this thread‐like fluke will deepen our thoughtful of avian schistosomiasis epidemiology and lead to more effective HCD control in the region.ObjectivesTo determine the life cycle of nasal Trichobilharzia in aquatic birds as well as aquatic snails and also identify the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The analyses conducted so far have been based on three gene regions, including 28S, the internal transcribed spacer (ITS) and the mitochondrial cox1. The investigations have confirmed that the nuclear ITS regions proved effective in delineating among Trichobilharzia species that are responsible for outbreaks of cercarial dermatitis ( Davis, Blair & Brant, 2021 ; Japa et al, 2021 ; Lashaki et al, 2023 ; Ashrafi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 64%
“…The analyses conducted so far have been based on three gene regions, including 28S, the internal transcribed spacer (ITS) and the mitochondrial cox1. The investigations have confirmed that the nuclear ITS regions proved effective in delineating among Trichobilharzia species that are responsible for outbreaks of cercarial dermatitis ( Davis, Blair & Brant, 2021 ; Japa et al, 2021 ; Lashaki et al, 2023 ; Ashrafi et al, 2021 ).…”
Section: Introductionmentioning
confidence: 64%